Implementation of Greedy Algorithm for Profit and Cost Analysis of Swallow's Nest Processing Dirty to Finished Products - Efendi Efendi; Daniel Ryan Hamonangan Sitompul; Stiven Hamonangan Sinurat; Ruben Ruben; Andreas Situmorang; Dennis Jusuf Ziegel; Julfikar Rahmad; Evta Indra (INFOKUM, 2022)
Swallow's nest is made from the saliva of swallows, especially species of swallows of the genus Collocalia. Swallow's nest is used traditionally to improve health so it is widely consumed by the community. Swallow nest products are difficult to produce, causing the product to be expensive. This study aims to analyze the costs and benefits of swallow nest production. The analysis uses the Greedy algorithm, which is looking for solutions to each stage of production. The principle of Greedy's algorithm is "take what you can get now". There are 6 processes in the production of swiftlet nests, namely sorting raw materials, cleaning, drying, printing, in process control (IPC) and packaging. In the sorting and cleaning process, employees in the medium and medium to light nest categories were combined. The total costs incurred in the sorting process are reduced by 14% and the costs incurred in the cleaning process are reduced by 8%. The process of drying dense and medium hair nests takes the same time so that they are carried out simultaneously and the required cost is reduced by 11% to Rp 675,000. The stages of printing the original and super types of nests are combined because they have.